Selected aspects of nursing care for an elderly patient with chronic obstructive pulmonary disease - Budnik, Marta; Galikowska, Anna; Marzec, Izabela; Balcerak, Dominika; Kobus, Edyta; Posieczek, Zuzanna (Journal of Education, Health and Sport, 2017)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is one of the most common geriatric respiratory diseases. COPD is a complex disease entity which is characterised by progressive and irreversible bronchostenosis, caused mainly by smoking. Purpose: revealing the magnitude of hazard of COPD to people's health, defining health problems of older people affected by COPD and the role of the nurse in looking after them. Materials and method: 15 scientific articles and contemporary literature, regarding nursing care in chronic obstructive pulmonary disease, were analysed. The key words used: chronic obstructive pulmonary disease, COPD, caring problems, nursing care. Results: nursing care for COPD-affected patients is the result of specific symptoms of this disease. The main assumptions of nursing care are: reducing the dyspnoea intensification, increasing the effectiveness of expectoration and neutralising the risk of complications. <span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Conclusions:<span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> COPD is one of the most severe social diseases in the world, where the older people constitute the highest number of affected patients. Its advanced stadium leads to respiratory disorder and death, which is why preventive measures, aimed at quitting smoking, play such a crucial role. Quitting smoking is supposed to prevent the ilness from occurring, stop its progress or counter the occurrence of complications. The role of the nurse in care for COPD-affected patients is passing broadly defined knowledge to them and their families and acting to help fight the disease.